Evaluation of the implementation of the hospital management information system (SIMRS) using the hot fit method: Systematic review - Munjirin, Munjirin; Intisari, Arih Diyaning; Aji, Budi (Science Midwifery, 2024)
Introduction: This research is motivated by the importance of implementing a hospital management information system (SIMRS) because it is important to assess its effectiveness, identify areas of improvement, and ensure that the system meets the specific needs and goals of the hospital. HOT FIT is a method that reviews the overall use of the system, namely humans, organizations, technology and benefits (Net Benefit). Method: This research is a study literature using the PRISMA diagram approach, with article searches using the research databases Pubmed, Science Direct, Google Scholar, and Scopus from 2018-2024. Results: A total of 10 relevant articles related to the application of SIMRS. Based on the results of the review of the article, it shows that human, organizational and technological factors have an important role in ensuring the success of SIMRS implementation. There are factors that do not depend on each other in implementing SIMRS, namely information quality, service quality, user satisfaction, organizational structure and organizational environment. Conclusion: System quality, system utilization, and net benefit factors all impact the success of SIMRS implementation. And there is a need for additional research regarding other factors that influence the application of SIMRS in improving the quality of information systems.